2014
DOI: 10.1242/jcs.150276
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin matrix assembly is essential for cell condensation during chondrogenesis

Abstract: Mesenchymal cell condensation is the initiating event in endochondral bone formation. Cell condensation is followed by differentiation into chondrocytes, which is accompanied by induction of chondrogenic gene expression. Gene mutations involved in chondrogenesis cause chondrodysplasias and other skeletal defects. Using mesenchymal stem cells (MSCs) in an in vitro chondrogenesis assay, we found that knockdown of the diastrophic dysplasia (DTD) sulfate transporter (DTDST, also known as SLC26A2), which is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 53 publications
(70 reference statements)
1
51
0
Order By: Relevance
“…PNA staining of the fli1a:eGFP + PCCs showed that mesenchymal condensations were equally detectable in miR-27 morphants and control embryos at 48 hpf (data not shown). Next, we analyzed the distribution of the extracellular matrix (ECM) protein fibronectin which is highly expressed during mesenchymal condensation (Hall and Miyake, 2000; Singh and Schwarzbauer, 2014). PCCs in both morphants and control embryos had equal fibronectin matrix distribution at 48 hpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PNA staining of the fli1a:eGFP + PCCs showed that mesenchymal condensations were equally detectable in miR-27 morphants and control embryos at 48 hpf (data not shown). Next, we analyzed the distribution of the extracellular matrix (ECM) protein fibronectin which is highly expressed during mesenchymal condensation (Hall and Miyake, 2000; Singh and Schwarzbauer, 2014). PCCs in both morphants and control embryos had equal fibronectin matrix distribution at 48 hpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fibronectin-dependent cellular self-assembly is emerging as a common morphological process, as it has been observed in several cell types, including primary fibroblasts [16], a variety of cell lines [5, 54], as well as mixed cell populations [57]. Recent studies have demonstrated a role for fibronectin matrix assembly in mesenchymal stem cell condensation [58], while other studies suggest that disruption of fibronectin-mediated cohesion may play a role in tumor metastasis [59]. As such, understanding how cell-substrate adhesion parameters cooperate with fibronectin matrix assembly to dynamically regulate the level of tissue or tumor cohesion or dyscohesion has implications in a variety of physiological and pathological processes, and may provide new avenues for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The early events in chondrogenic differentiation such as cell condensation and changes in gene expression are recapitulated in a micromass culture system using mesenchymal stem cells [24]. We showed that cell aggregation depends on FN matrix assembly [25]. As mesenchymal stem cells condense, FN and N-cadherin levels are up-regulated and matrix assembly increases.…”
Section: Synergy Between Fn-integrin and Homophilic Cadherin Interactmentioning
confidence: 99%
“…During this period, cells proliferate and initiate the differentiation program, which requires induction of the Sox9 transcription factor, which is essential for cartilage-specific gene expression. Either the blockade of FN polymerization [25] or the knockdown of N-cadherin [26] in micromass cultures prevents cell condensation. Incomplete condensation prevents up-regulation of Sox9 expression and cell differentiation into chondrocytes.…”
Section: Synergy Between Fn-integrin and Homophilic Cadherin Interactmentioning
confidence: 99%